On RFG-Closed Sets in Topological Spaces (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we introduce and study the new class of sets, namely Regular Feebly Generalized Closed (briefly \(RFG\)-closed) sets, Regular Feebly Generalized neighborhoods (briefly \(RFG\)-nbhd), \(RFG\)-interior and \(RFG\)-closure in topological spaces and also some properties of new concepts have be en studied.
Keywords: \(RFG\)-closed sets; \(RFG\)-nighborhoods; \(RFG\)-interior and \(RFG\)-closure